Mass support for proposals to reshape policing depends on the implications for crime and safety - Vaughn, Paige E. (Criminology & public policy, 2022)
This paper presents novel survey and experimental evidence that reveals the mass public's interpretation of movements to reform, defund, and abolish the police. We find strong support for police reform, but efforts to defund or abolish generate opposition both in terms of slogan and substance. While these differences cannot be explained by differing beliefs about each movement's association with violent protests, racial makeup, or specific programmatic changes, efforts to defund and abolish the police appear unpopular because they seek reduced involvement of police in traditional roles and cuts in police numbers.